Lipid-lowering effects of Coffea arabica pulp aqueous extract in Caco-2 cells and hypercholesterolemic rats - Atcharaporn Ontawong (2018)
© 2018 Elsevier GmbH Background: Coffea arabica pulp (CP) is the first by-product obtained from coffee berries during coffee processing. The major constituents of CP, including chlorogenic acid, caffeine, and epicatechin exhibit anti-hyperlipidemic effects in in vitro and in vivo models. Whether Coffea arabica pulp aqueous extract (CPE) has a lipid-lowering effect remains unknown. Purpose: This study examined the effect of CPE on cholesterol absorption, and identified the mechanisms involved in lowered cholesterol in in vitro and in vivo models. Methods: Uptake of [3H]-cholesterol micelles and the mode of CPE inhibition were determined using human intestinal Caco-2 cells, and subsequently, confirmed using isolated rat jejunal loops. In addition, the 12-week high-fat diet-induced hypercholesterolemic rats (HF) received either CPE (1000 mg/kg BW), a sole and high dose which was selected because it contained approximately 12 mg of CGA that was previously shown to have lipid-lowering effects, or ezetimibe (10 mg/kg BW), a cholesterol inhibitor. The rats were divided into HF, HF ++ CPE, and HF ++ ezetimibe groups for the next 12 weeks. Normal rats received a normal diet (ND) and CPE (ND + CPE). Body weights and lipid profiles were evaluated. Cholesterol transporter, Niemann–Pick C1-Like 1 (NPC1L1), protein expression and liver X receptor alpha (LXRα) mRNA expression were determined. In vitro micellar complex properties were also investigated. Results: CPE inhibited [3H]-cholesterol micelle transport in Caco-2 cells and rat jejunal loops in a dose-dependent, non-competitive manner partly by decreasing membrane NPC1L1 expression. Congruently, CPE and its major constituents activated LXRα which, in turn, down-regulated NPC1L1. Furthermore, CPE interfered with physicochemical characteristics of cholesterol mixed micelles. These data were consistent with decreased body weight and slowed body weight gain and improved lipid profiles by CPE in hypercholesterolemic rats while no change occurred in these parameters in normal rats. Down-regulated intestinal NPC1L1 expression mediated by increased LXRα mRNA were also observed in HF ++ CPE and ND + CPE rats. Conclusion: CPE has a cholesterol-lowering effect in in vitro and in vivo via inhibition of intestinal cholesterol absorption by down-regulating NPC1L1 mediated LXRα activation and interfering with micellar complex formation. Accordingly, CPE could be developed as nutraceutical product to prevent dyslipidemia-induced obesity and insulin resistance.